2020
DOI: 10.2217/pmt-2020-0033
|View full text |Cite
|
Sign up to set email alerts
|

10-kHz Spinal Cord Stimulation Treatment for Painful Diabetic Neuropathy: Results from Post-Hoc Analysis of the SENZA-PPN Study

Abstract: Aim: Previous studies of 10 kHz spinal cord stimulation demonstrated its safety and efficacy for treatment of neuropathic pain of the trunk and/or limbs. This study analyzed data from a subset of subjects with painful diabetic neuropathy enrolled in a prospective, multicenter study of peripheral polyneuropathy with various etiologies. Materials & methods: Of the eight subjects that had permanent devices, seven attended the 12-month follow-up assessment. Results & conclusion: At 12 months, 6/7 subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 36 publications
4
42
0
Order By: Relevance
“…In addition, an analysis of patients with painful diabetic neuropathy enrolled in a prospective, multicentre study of peripheral polyneuropathy found that five out of seven patients showed improvements in sensory perception and reflexes. 25 Similarly, a case series involving patients with painful diabetic polyneuropathy reported either preservation or improvement in sensory perception in their lower limbs following treatment with 10 kHz SCS. 26 These results together with our findings suggest that 10 kHz SCS may have beneficial effects in addition to pain relief.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, an analysis of patients with painful diabetic neuropathy enrolled in a prospective, multicentre study of peripheral polyneuropathy found that five out of seven patients showed improvements in sensory perception and reflexes. 25 Similarly, a case series involving patients with painful diabetic polyneuropathy reported either preservation or improvement in sensory perception in their lower limbs following treatment with 10 kHz SCS. 26 These results together with our findings suggest that 10 kHz SCS may have beneficial effects in addition to pain relief.…”
Section: Discussionmentioning
confidence: 96%
“…Spinal cord stimulation at 10 kHz is associated with improved clinical outcomes in patients with various chronic pain etiologies, while also improving QOL and reducing opioid intake. 34,57,[62][63][64][65][66][67][68][69][72][73][74][75][76][77][78][79][80][81][82][83] The primary aim of this review was to summarize the existing clinical evidence for the use of 10 kHz SCS to treat chronic back and/or leg pain.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, paresthesia itself is a limiting factor for a substantial number of patients, particularly paresthesia affecting areas outside of the painful region and carrying intensity variations resulting from postural changes [86]. Alternative waveforms have been developed with the aim of addressing some of these limitations and have been studied in patients with PDN, including burst SCS and high-frequency SCS [62][63][64]87,88].…”
Section: Conventional Scsmentioning
confidence: 99%
“…In contrast to conventional and burst SCS, evidence from a multicenter RCT has shown that high-frequency SCS delivered at 10 kHz (10 kHz SCS) produces deep and durable paresthesia-free pain relief for chronic neuropathic pain [44,[62][63][64]88,[91][92][93][94][95][96][97]. The specific benefits and unique physiological responses associated with 10 kHz SCS may be attributed to its unique mechanism of action [98][99][100][101][102][103][104][105], although the precise mechanism of action is not yet understood [106].…”
Section: High Frequency (Or 10 Khz) Scsmentioning
confidence: 99%
See 1 more Smart Citation